Remarkable response to low dose of selpercatinib in a patient with RET-rearranged non-small cell lung cancer - Jun Sakakibara-Konishi; Hirofumi Takahashi; Kenichiro Ito; Tomoo Ikari; Yasuyuki Ikezawa; Hidenori Kitai; Megumi Furuta; Yuta Takashima; Tetsuaki Shoji; Masahide Fukudo; Satoshi Konno (Respiratory Medicine Case Reports)
Chromosomal rearrangements of the RET (rearranged during transfection) gene are detected in approximately 1–2% of non-small cell lung cancers (NSCLC) and have function as oncogenic driver genes. Selpercatinib is a highly effective RET inhibitor for RET-rearranged patients with NSCLC and shows mostly tolerable adverse events. However, hypertension, aspartate aminotransferase increase, and alanine aminotransferase increase are the most common adverse events, and dose modification or discontinuation is required occasionally. Here, we describe a case who has response to 40 mg of selpercatinib every other day because the dose had to be adjusted owing to adverse events such as liver dysfunction. Dose modification of selpercatinib, according to adverse event incidences, may be considered, as selpercatinib may be effective in some cases even at very low concentrations.